Community Resilience: A Perspective from Latin America and the Caribbean - Gonzales-Iwanciw, Javier; Guáqueta, Victoria; Castañeda, Edna; Le Coq, Jean-François; Postigo, Julio C (Springer, 2021)
Communities are increasingly confronted with the simultaneous effects of climate and socioeconomic changes in different geographical and cultural contexts of Latin America and the Caribbean. See level rise, changes in temperature and rainfall patterns, extreme climate events, and outbreak of diseases are deteriorating and putting at risk the community livelihoods of vulnerable populations.